2017
DOI: 10.18632/oncotarget.22922
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional tumor model mimics stromal - breast cancer cells signaling

Abstract: Tumor stroma is a major contributor to the biological aggressiveness of cancer cells. Cancer cells induce activation of normal fibroblasts to carcinoma-associated fibroblasts (CAFs), which promote survival, proliferation, metastasis, and drug resistance of cancer cells. A better understanding of these interactions could lead to new, targeted therapies for cancers with limited treatment options, such as triple negative breast cancer (TNBC). To overcome limitations of standard monolayer cell cultures and xenogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 109 publications
(102 reference statements)
1
35
0
Order By: Relevance
“… The patterned tumor spheroids partially addressed challenges in the heterogeneity of spheroid culture in vitro, which is therefore used as promising platforms for executing high‐throughput anticancer compounds screening. The ability to scale‐up 3D spheroid culture in microfluidic devices offers new opportunity for fast testing of multiple anticancer drugs and analyze their half‐maximum (IC 50 ) and maximum ( E max ) inhibitory concentrations, which facilitates the multiparametric analysis of cellular responses to drug compounds and identify novel chemical probes with chemotherapeutic benefits, as demonstrated in Figure 26e …”
Section: Applications: Toward Functional Artificial Llpsmentioning
confidence: 99%
“… The patterned tumor spheroids partially addressed challenges in the heterogeneity of spheroid culture in vitro, which is therefore used as promising platforms for executing high‐throughput anticancer compounds screening. The ability to scale‐up 3D spheroid culture in microfluidic devices offers new opportunity for fast testing of multiple anticancer drugs and analyze their half‐maximum (IC 50 ) and maximum ( E max ) inhibitory concentrations, which facilitates the multiparametric analysis of cellular responses to drug compounds and identify novel chemical probes with chemotherapeutic benefits, as demonstrated in Figure 26e …”
Section: Applications: Toward Functional Artificial Llpsmentioning
confidence: 99%
“…These cytokines are known to promote chemoresistance (Mao et al, 2015; Su et al, 2018). Another coculture model used to study chemoresistance to paclitaxel (PTX), is an aqueous two‐phase system (ATPS) engineered by robotically dispensed MDA‐MB‐231 cells with matched donor human mammary fibroblasts and CAFs (1:2 TNBC:stromal) in a DEX‐phase nanodrop (Ham et al, 2018). The incorporation of CAFs was important as this has been previously reported to contribute to MDA‐MB‐231 chemoresistance in 2D (Amornsupak et al, 2014; Goliwas et al, 2017).…”
Section: Multicellular Spheroid Modelsmentioning
confidence: 99%
“…The incorporation of CAFs was important as this has been previously reported to contribute to MDA‐MB‐231 chemoresistance in 2D (Amornsupak et al, 2014; Goliwas et al, 2017). ATPS study revealed that the signaling between the CXCL12 cytokine secreted by CAFs and the associated receptor CXCR‐4 activated the MAPK/PI3K pathway driving proliferation and drug resistance (Ham et al, 2018). In another coculture study, Brancato et al (2018) compared the applicability of the basic spheroid model to a 3D microtissue (3D‐μTP) scaffold in which the cells spread throughout a porous gelatin microbead to test the efficacy of DOX on MCF7 breast cancer cells with and without incorporation of CAFs (Brancato et al, 2018).…”
Section: Multicellular Spheroid Modelsmentioning
confidence: 99%
“…Thus, 3D cell cultures, such as spheroids, have received great attention from the research community, as these in vitro models can represent more accurately the different properties of human tissues, such as liver (Yoon, Lee, Lee, & Lee, 2015), thyroid *Elisabete C. Costa and Daniel N. Silva contributed equally to this work. (Cirello et al, 2017), cartilage (Jukes et al, 2008), pancreatic tissue (Lumelsky et al, 2001), cardiac muscle (Kehat et al, 2001) or of solid tumors (e.g., breast, colon, pancreas, prostate, ovary, among others (Eiraku et al, 2008;Eiraku et al, 2011;Ham et al, 2018;Ham, Joshi, Luker, & Tavana, 2016;Hamilton, 1998;Khawar et al, 2018;Lazzari et al, 2018;Suga et al, 2011)). Spheroids are microtissues with a diameter within hundreds of micrometers to few millimeters that present a spatial architecture, cellular organization, cell-cell, and cell-extracellular matrix interactions quite similar to those found in the human tissues (as reviewed in detail elsewhere (Costa et al, 2016;Duval et al, 2017)).…”
Section: Introductionmentioning
confidence: 99%